2008
DOI: 10.1212/01.wnl.0000316800.22949.20
|View full text |Cite|
|
Sign up to set email alerts
|

Multimechanistic (sumatriptan-naproxen) early intervention for the acute treatment of migraine

Abstract: The fixed-dose single-tablet formulation of sumatriptan/naproxen was effective and well tolerated in an early intervention paradigm for the acute treatment of migraine, including traditional and nontraditional symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 34 publications
3
34
0
1
Order By: Relevance
“…Although significantly fewer female participants treating with sumatriptan-naproxen used rescue medication compared with placebo in this study, the overall incidence of rescue medication was higher than that reported previously in early intervention studies that included both men and women. 12,13 Although the majority of participants in the current studies attributed their use of rescue medication to "migraine," the coexistence of menstrual pain may influence the use of pain medication.…”
Section: Discussionmentioning
confidence: 90%
“…Although significantly fewer female participants treating with sumatriptan-naproxen used rescue medication compared with placebo in this study, the overall incidence of rescue medication was higher than that reported previously in early intervention studies that included both men and women. 12,13 Although the majority of participants in the current studies attributed their use of rescue medication to "migraine," the coexistence of menstrual pain may influence the use of pain medication.…”
Section: Discussionmentioning
confidence: 90%
“…Pain-free efficacy of migraine pharmacotherapy appears to be enhanced, and the incidence of adverse events appears to be reduced by the practice of early intervention [Goadsby et al 2008;Silberstein et al 2008;Mathew et al 2007;Carpay et al 2004;Brandes et al 2005;Loder et al 2005;Mathew et al 2004;Scholpp et al 2004;Cady et al 2000]. These caveats notwithstanding, the results demonstrate the better performance of sumatriptan/naproxen sodium to sumatriptan monotherapy, naproxen sodium monotherapy and placebo with respect to the rigorous clinical endpoint of sustained pain-free/no adverse events and reinforce the usefulness of utilizing this new composite endpoint.…”
Section: Discussionmentioning
confidence: 67%
“…The combination was more effective than either sumatriptan 85 mg or naproxen 500 mg alone [83,84]. Interestingly, sumatriptan 85mg was not superior to naproxen 500 mg.…”
Section: Combination Therapy Strategiesmentioning
confidence: 90%
“…At 2 h, 52 and 51% of sumatriptan/naproxen-treated patients were pain free, as compared with 17% and 15% of placebo-treated patients (p < 0.001) [84].…”
Section: Treatment Of Mild Versus Moderate-to-severe Intervention Strmentioning
confidence: 90%